2021
DOI: 10.1002/adfm.202108104
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Transition Metal Chalcogenide Nb2Pd3Se8: A New Candidate of 1D Van der Waals Materials for Field‐Effect Transistors

Abstract: In this work, high-quality 1D van der Waals (vdW) Nb 2 Pd 3 Se 8 is synthesized, showing an excellent scalability from bulk to single-ribbon due to weakly bonded repeating unit ribbons. The calculation of electronic band structures confirmed that this novel Nb 2 Pd 3 Se 8 is a semiconducting material, displaying indirect-to-direct bandgap transition with decreasing the number of unit-ribbons from bulk to single. Field effect transistors (FETs) fabricated on the mechanically exfoliated Nb 2 Pd 3 Se 8 nanowires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…To further quantitatively explore the different periodicity of Raman intensities, the polarization Raman was studied . The Raman scattering intensity from the vibration modes are defined as I ∝ | e i · R · e s |, where R represents the Raman tensor, and e i and e s correspond to the polarization vector of the incident light and scattered light, respectively. The polarization vectors are (0, cos θ, sin θ) for both the incident and scattering light, and the Raman tensors of active modes could be analyzed as follows normalA normalg = ( true a d 0 d b 0 0 0 c ) goodbreak0em1em⁣ normalB normalg = ( true 0 0 e 0 0 f e f 0 ) where a–f represent the Raman tensor elements. The Raman intensity of the A g and B g modes under parallel polarization configurations are indicated as I A g | b | 2 cos 4 θ + | c | 2 sin 4 …”
Section: Resultsmentioning
confidence: 99%
“…To further quantitatively explore the different periodicity of Raman intensities, the polarization Raman was studied . The Raman scattering intensity from the vibration modes are defined as I ∝ | e i · R · e s |, where R represents the Raman tensor, and e i and e s correspond to the polarization vector of the incident light and scattered light, respectively. The polarization vectors are (0, cos θ, sin θ) for both the incident and scattering light, and the Raman tensors of active modes could be analyzed as follows normalA normalg = ( true a d 0 d b 0 0 0 c ) goodbreak0em1em⁣ normalB normalg = ( true 0 0 e 0 0 f e f 0 ) where a–f represent the Raman tensor elements. The Raman intensity of the A g and B g modes under parallel polarization configurations are indicated as I A g | b | 2 cos 4 θ + | c | 2 sin 4 …”
Section: Resultsmentioning
confidence: 99%
“…Notably, the exfoliated 1D Ta 2 Ni 3 Se 8 ACs demonstrated the ambipolar semiconducting behavior, 36 whereas the Ta 2 Pd 3 Se 8 and Ta 2 Pt 3 Se 8 ACs were found to exhibit n-type and p-type semiconducting characteristics, respectively. 49,71 It is unusual to observe different transport polarities in one isostructural material system, which can be conveniently integrated into complementary electronics (Figure 3c). 72 Also, the ambipolar semiconducting Ta 2 Ni 3 Se 8 ACs, featured with the differential transconductance under positive/negative gate bias, can enable the higher data processing capability in a single device, thus significantly simplifying the circuit design.…”
Section: Electronics Of Atomic Chainsmentioning
confidence: 99%
“…In this study, we first demonstrated the chemical doping of Nb 2 Pd 3 Se 8 , which is a representative n-type 1D vdW material, 21 through chemically doping AuCl 3 and β-nicotinamide adenine dinucleotide (NADH) as p-type and n-type dopants, respectively. The concentration of holes and electrons controlled by varying the immersion time in the doping solution were effectively confirmed by spectroscopic and transport studies.…”
mentioning
confidence: 99%
“…As proven in previous studies, the Nb 2 Pd 3 Se 8 unit ribbons are connected in a zigzag shape, and the specific interaction between the terminating Pd atoms and the trans-Se atoms in the adjacent unit ribbons is 0.39 eV/ atom in binding energy at a distance of 0.26 nm, comparable to the hydrogen bond-type vdW interaction. 21,27 In the region of n-type doping, two electrons were donated from NADH to Nb 2 Pd 3 Se 8 as the oxidation of NADH progressed by the reaction of two-electrons one-proton: NADH ↔ NAD + + H + + 2e − . 28 Since electron donation was achieved by pyrolysis of NADH, we heated the substrate at 150 °C for 3 min after dipping it in the NADH solution.…”
mentioning
confidence: 99%